2021
DOI: 10.1038/s41598-021-91324-x
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity attenuates the associations of systemic immune-inflammation index with total and cause-specific mortality among middle-aged and older populations

Abstract: Systemic immune-inflammation index (SII) emerged as a biomarker of chronic inflammation and an independent prognostic factor for many cancers. We aimed to investigate the associations of SII level with total and cause-specific mortality risks in the general populations, and the potential modification effects of lifestyle-related factors on the above associations. In this study, we included 30,521 subjects from the Dongfeng-Tongji (DFTJ) cohort and 25,761 subjects from the National Health and Nutrition Examinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…Other researchers think it can be used as an indicator of the progression of a certain disease. The study by Li et al [ 13 ] suggested that high SII levels may increase overall mortality and cardiovascular disease mortality in the general population, using NHANES follow-up data from 1999 to 2014. He et al [ 12 ] showed a correlation between SII and all-cause mortality in the US arteriosclerotic cardiovascular disease (ASCVD) population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other researchers think it can be used as an indicator of the progression of a certain disease. The study by Li et al [ 13 ] suggested that high SII levels may increase overall mortality and cardiovascular disease mortality in the general population, using NHANES follow-up data from 1999 to 2014. He et al [ 12 ] showed a correlation between SII and all-cause mortality in the US arteriosclerotic cardiovascular disease (ASCVD) population.…”
Section: Discussionmentioning
confidence: 99%
“…It is calculated using a formula that takes into account the levels of certain immune system markers in the blood, The calculation formula is platelets × neutrophils ÷ lymphocytes [ 11 ]. The SII is often used as a predictor of mortality in patients with tumors, as higher SII values have been associated with an increased risk of death [ 10 , 12 , 13 ]. This may be related to the imbalance between the body’s tumor-promoting and anti-tumor factors in the tumor state.…”
Section: Introductionmentioning
confidence: 99%
“…According to the instructions for using NHANES data, we accounted for complex survey design factors, such as clustering, stratification, and dietary weight at day one of the survey [18]. Public-use Linked Mortality Files contain the follow-up time from the in-person interview survey, and were used to assess person-time to death [19]. For continuous variables, means and standard errors were presented, while counts and proportions (after weighting) were presented for categorical variables [20].…”
Section: Discussionmentioning
confidence: 99%
“…The blood analyzer provided white blood cell count, neutrophil count, lymphocyte count, and neutrophil-to-lymphocyte ratio (NLR). We additionally computed two hematological indexes for systemic in ammation, the systemic immunein ammation index (SII) and the aggregate index of systemic in ammation (AISI), using the following formulae 29,30 : SII = neutrophil x platelet/lymphocyte count AISI = neutrophil x monocyte x platelet/lymphocyte count.…”
Section: Serum In Ammatory Biomarker Measuresmentioning
confidence: 99%